STRUKTUR SEMANTIK KONSEP MANUSIA DALAM AL-QUR'AN - Nahdiyyin, Khairon (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
Semantic analysis on the human structure in The Koran is always interesting to be discussed, especially the one related to the human characterization with its entire symbolical characteristics embedded to the vocabularies applied to them. Human being, in Koran, is termed in many words â€œIns, Basyar, Insan, Bani Adam and Naasâ€. This article does not show the relation between human characters, male and female. Instead, it limits the discussion on the human being portrayed by Koran not considering the division of male and female. In this phase, male and female are the same. They are not burdened by unique load for each male and female human being. Instead, they are given characteristics as human being according to the existence. Existentially, it can be said that human being is a group of living creatures among the other Godâ€™s creatures that is divided into two kinds, jin group and ins group. The ins group is the combination between basyar and insan. The first form of human being is Adam who bring forth the descendant so that all human being born after him is called bani Adam. The descendants of Adam living in the nowadays space and time in called naas. Ins, basyar, insan and bani Adam is a particular concept of human being. Such concept is used by God to remind human being, naas, to always remember to their characteristics that they are ins, basyar, insan and bani Adam. They are bounded to the consequence of the concept.